Pengaruh Kualitas Pelayanan Dan Kinerja Karyawan Frontliner Terhadap Kepuasan Nasabah PT Bank Rakyat Indonesia (Persero), Tbk Kantor Cabang Balikpapan Sudirman Unit Klandasan - Totok Ismawanto; R Gunawan Setianegara; Safirda Rahmani (Jurnal Bisnis dan Kewirausahaan, 2020)
The main purpose of this research is to find out whether there is an influence of service quality variables and frontliner employee performance simultaneously on customer satisfaction of PT Bank Rakyat Indonesia (Persero) Tbk, Balikpapan Sudirman Unit Klandasan Branch Office. Besides that, whether partially the quality of service variables and the performance of frontliner employees affect customer satisfaction of PT Bank Rakyat Indonesia (Persero) Tbk, Balikpapan Sudirman Unit Klandasan Branch Office. The problem in this study is the existence of customer complaints related to service at PT Bank Rakyat Indonesia (Persero) Tbk in the Office of the Klandasan Unit, and there are differences in the results of previous studies related to the variables discussed. The research method used is quantitative descriptive. The independent variable of this study is the quality of service (X1) and frontliner employee performance (X2) at PT Bank Rakyat Indonesia (Persero), Tbk Balikpapan Branch Office Sudirman Klandasan Unit. The dependent variable (Y) is customer satisfaction at the same bank. The population used is all customers of PT. Bank Rakyat Indonesia (Persero), Tbk Balikpapan Branch Office Sudirman Klandasan Unit, with a total of 12,375 customers. With a simple random sampling technique, and using the Slovin formula 100 random samples were taken from the entire population. Data is collected through observations and questionnaires. Data analysis used validity test, reliability test, classic assumption test, multiple linear test, coefficient of determination test, F test and t test. The results of the study concluded that both simultaneous and partial frontliner employee performance variables and service quality affect customer satisfaction. This is consistent with the results of the test calculations that have been done with data sourced from primary data with the spss application. From the calculation of the calculated F value obtained by 45.103> F table of 3.09; and t test results of the variable service quality (X1) of 3.163, and employee performance (X2) of 2.088> 1.984. Likewise, the significance, service quality variable (X1) is 0.002 and frontliner employee performance (X2) is 0.039 smaller than 0.05, which means there is a partially significant influence between employee performance variables and service quality with customer satisfaction variables.